Identifying Small-Molecule Inhibitors of SARS-CoV-2 RNA-Dependent RNA Polymerase by Establishing a Fluorometric Assay - Bai, Xiaoming; Sun, Hongmin; Wu, Shuo; Li, Yuhuan; Wang, Lifei; Hong, Bin (Frontiers in Immunology, 2022)
SARS-CoV-2 (severe acute respiratory syndrome coronavirus‐2), a member of the coronavirus family appeared in 2019, has caused the largest global public health and economic emergency in recent history affecting almost all sectors of society. SARS-CoV-2 is a single-stranded positive-sense RNA virus rely on RNA‐dependent RNA polymerase (RdRp) activity in viral transcription and replication. Due to its high sequence and structural conservation in coronavirus and new SARS-CoV-2 variants, RdRp has been recognized as the key therapeutic target to design novel antiviral strategies. Nucleotide analogs (NAs), such as remdesivir, is the most promising class of RdRp inhibitors to be used in the treatment of COVID-19. However, the presence of exonucleases in SARS-CoV-2 caused a great challenge to NAs, the excision of incorporated NAs will lead viral resistance to this group of inhibitors. Here, we expressed active RdRp protein both in a eukaryotic expression system of baculovirus-infected insect cells and a prokaryotic expression system of Escherichia coli cells. Nsp7 and nsp8 of the functional RdRp holoenzyme were generated in Escherichia coli. An in vitro RdRp activity assay has been established with reconstituted nsp12/nsp7/nsp8 complex and biotin labeled self-priming RNAs, and the activity of RdRp complex was determined by detecting binding and extension of RNAs. Moreover, to meet the needs of high-throughput drug screening, we developed a fluorometric approach based on dsRNA quantification to assess catalytic activity of RdRp complex which also suitable for testing in 96-well plate. We demonstrated that the active triphosphate form of remdesivir (RTP) and several reported non-nucleotide analog viral polymerase inhibitors blocked the RdRp in the in vitro RdRp activity assay and high-throughput screening model. This high-throughput screening model has been applied to a custom synthetic chemical and natural product library of thousands of compounds for screening SARS-CoV-2 RdRp inhibitors. Our efficient RdRp inhibitor discovery system provides a powerful platform for the screening, validation and evaluation of novel antiviral molecules targeting SARS-CoV-2 RdRp, particularly for non-nucleotide antivirals drugs (NNAs).